Association between statin use and risk of gallstone disease and cholecystectomy: a meta-analysis of 590,086 patients - Chang, Yu; Lin, Hong-Min; Chi, Kuan-Yu; Lin, Wan-Ying; Chou, Tsung-Ching (PeerJ, 2023)
Background Statins have been reported to reduce the risk of gallstone disease. However, the impacts of different durations of statin use on gallstone disease have not been clarified. The aim of this study is toperform a systematic review with meta-analysis to update and to elucidate the association between statin use and the risk of gallstone disease and cholecystectomy. Methods Medline, Embase and Cochrane Library were searched from the inception until August 2022 for relevant articles investigating the difference in the risk of gallstone disease between statin users and non-users (PROSPERO, ID: CRD42020182445). Meta-analyses were conducted using odds ratios (ORs) with corresponding 95% confidence intervals (CIs) to compare the risk of gallstone disease and cholecystectomy between statin user and nonusers. Results Eight studies enrolling 590,086 patients were included. Overall, the use of statins was associated with a marginally significant lower risk of gallstone disease than nonusers (OR, 0.91; 95% CI [0.82–1.00]). Further subgroup analysis showed that short-term users, medium-term users, and long-term users were associated with a significantly higher risk (OR, 1.18; 95% CI [1.11–1.25]), comparable risk (OR, 0.93; 95% CI [0.83–1.04]), and significantly lower risk of gallstone diseases (OR, 0.78; 95% CI [0.68–0.90]) respectively, compared to nonusers. Conclusions Patients with medium-term or long-term use of statins without discontinuation are at a lower risk of gallstone disease or cholecystectomy.
Keywords: Statin; Gallstone